Pengaruh Kualitas Pelayanan dan Kualitas Produk terhadap Kepuasan Pelanggan Shell di DKI Jakarta - Yunita Alifia; Siti Mabrur Rachmah (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study aims to analyze the effect of service quality and product quality on customer satisfaction of Shell gas stations in DKI Jakarta. Using a descriptive quantitative approach, data was collected through a questionnaire of 100 respondents who are Shell customers. The purposive sampling technique was used in the sample selection. The regression analysis results show that service quality and product quality have a positive and significant effect on customer satisfaction. This finding indicates that the better the quality of services and products provided, the higher the level of customer satisfaction. This research provides implications for Shell management to continue to improve service and product quality to maintain customer loyalty.